Parents' attachment orientation, interviewers' support, and children's memory for a mildly distressing event. Issue 10 (26th November 2021) - Chae, Yoojin; Goodman, Gail S.; Wang, Yan; Goodman, Miranda; McWilliams, Kelly; Shaver, Phillip R.; Thompson, Ross A.; Widaman, Keith F.
ABSTRACT: Parents' attachment orientations predict children's memory about distressing life events, such that parents who are less secure in close relationships tend to have children who are less accurate in their memory reports. This study examined whether socially supportive interviewing would reduce differences in children's memory performance associated with parents' attachment. Children (3 to 5 years, N  = 63) and their primary caretakers took part in the Preschool Attachment Classification System (PACS), a moderately distressing event for children of preschool age that is based on the Strange Situation Procedure. Children's memory for the event was then tested shortly thereafter by either a supportive or a non-supportive interviewer. In the non-supportive condition, children whose parents scored higher on attachment avoidance provided lower proportions of correct free recall. However, the association was not significant for children in the supportive condition. In addition, higher parental attachment anxiety predicted lower proportions of correct free recall for children of highly avoidant parents, but not for children of parents lower in attachment avoidance. For direct questions, age differences in proportion correct and proportion incorrect favoured older children. Findings provide insight into interviewing techniques at time of memory retrieval that benefit children of insecure parents.